Growing rich dietary nuts in Himalayas - Thakur, Nidhika; Singh, R K; Prakash, Om; Singh, Bijendra Kumar (Indian Horticulture, 2023)
The nuts like chestnut and hazelnut are rich in the dietary vitamins and minerals. They can be grown in the temperate region of the Himalayas. Since they are not grown in India on such a large scale due to inadequate knowledge about the nutritional benefits of these nuts, it is required to make the farmers of Himalayan region of India aware of the usefulness of these nuts. The areas of Uttarakhand, Himachal Pradesh and North East regions have good climatic conditions required for growing these nuts. Therefore, these nuts can be explored in such areas of India in order to improve the diversity in nuts production in these regions and also to increase the nutritional benefits to the people.